Successful pregnancy outcome in paroxysmal nocturnal hemoglobinuria (PNH) following escalated eculizumab dosing to control breakthrough hemolysis. Issue 1 (2015) - Sharma, Ruby; Keyzner, Alla; Liu, Johnson; Bradley, Thomas; Allen, Steven L.
Abstract: Pregnancy in women with paroxysmal nocturnal hemoglobinuria (PNH) is associated with increased maternal and fetal morbidity and mortality. There is limited published experience regarding therapy of PNH during pregnancy. We describe a case of a 30 year old female with hypoplastic myelodysplastic syndrome and PNH. After two years of treatment with eculizumab, she became pregnant. She developed breakthrough hemolysis at 20 weeks gestation. Pharmacokinetic and pharmacodynamic studies demonstrated a subtherapeutic eculizumab level with absence of complement blockade. Escalation of her eculizumab dose successfully controlled hemolysis and restored therapeutic eculizumab level and activity. She delivered a healthy baby at 36 weeks. Graphical abstract: Highlights: Pregnancy in PNH cause increased maternal and fetal morbidity & mortality. Limited published data regarding the use of eculizumab in pregnancy. Breakthrough hemolysis in pregnancy despite standard eculizumab administration. Escalated dose of eculizumab is required to achieve therapeutic eculizumab levels.